Taksiran kerugian produksi daging akibat infeksi cacing saluran pencernaan pada sapi ongole Indonesia - Simon HE; Elok Budi Retnani; Lily Zalizar (Hemera Zoa, 1991)
One hundred and ten males of Ongole cattle were recorded for their carcass weights at slaugter and their faccal samples were assayed for worm eggs. Significant negative correlation (r) with determination coefficient (r2) 0.2754 was found between the numbers of worm eggs in the faeces and the cattle carcass weight 151.5 kg were found infected with nematodes only, worm eggs.